Functional Selenium Nanoparticles Enhanced Stem Cell Osteoblastic Differentiation through BMP Signaling Pathways. (1st September 2014) - Zheng, Chuping; Wang, Jinsheng; Liu, Yanan; Yu, Qianqian; Liu, Ying; Deng, Ning; Liu, Jie
<x xml:space="preserve">Abstract</x> Stem cells have generated a great deal of excitement in tissue engineering and regenerative medicine, and it is important to understand the interaction mechanisms between nanomaterials and mesenchymal stem cells (MSCs) for biomedical applications. In this study, ruthenium (II) functional selenium nanoparticles (Ru@Se) are used for stem cell research. Specifically, Ru@Se are compared with citric acid selenium nanoparticles (Cit@Se)to identify their effects on MSCs differentiation and associated molecular mechanism. These data suggest that the effective adsorbing abilities of Ru@Se and Cit@Se allow them to act as preconcentration materials for osteogenic chemical inducers, which accelerates MSCs differentiation into osteoblasts. Further results suggest that selenium nanoparticles enhance the differentiation of MSCs toward osteogenic lineage over adipocytes by promoting osteogenic transcription and attenuating adipogenic transcription. Ru@Se and Cit@Se exert these effects by activating Smad‐dependent BMP signaling pathway, which regulates the expression of relevant genes to induce osteogenic differentiation.